Combined use of super‐oxidised solution with negative pressure for the treatment of pressure ulcers: case report. Issue 3 (24th May 2012) - de Angelis, Barbara; Lucarini, Lucilla; Agovino, Annarita; Migner, Alessia; Orlandi, Fabrizio; Floris, Micol; Cervelli, Valerio; Curcio, Cristiano
<x xml:space="preserve">Abstract</x> A 61‐year‐old patient was affected by flaccid paraplegia for 20 years because of post‐traumatic medullar injury caused by an accidental fall, with stage IV sacral pressure ulcer for 3 years. The patient later developed stage IV sacral pressure ulcer. After 6 months, a new granulation tissue formation appeared in the wound and a reduction of its diameter was observed (length 20 cm, width 15 cm, depth 5 cm). We therefore treated the wound with PRP (platelet rich plasma) intra‐lesion and peri‐lesional injections. The wounds were covered with three‐dimensional polymerised hyaluronic acid medicated biologic dressing. After the surgery, a moderate reduction in diameter and the depth was observed. Super‐oxidised solution (SOS‐Dermacyn) was applied to control infection locally together with negative pressure to control the exudate and the local bacteremia, to avoid infectious complications without application of systematic antibiotic therapy.